2005
DOI: 10.1007/s10517-005-0257-7
|View full text |Cite
|
Sign up to set email alerts
|

Disorders in Cytokine Gene Expression in Endometrial Hyperplasia and Effect of Hormone Therapy

Abstract: We studied local expression of insulin-like growth factor 1, insulin-like growth factor receptor, epithelial growth factor, transforming growth factor beta2, PCNA, TNF-alpha, type I TNF receptor, Fas, FasL, IFN-gamma, IL-1beta, IL-4, IL-6, IL-8, IL-10, and IL-12 genes in intact and hyperplastic endometrium. Endometrial hyperplasia was associated with reduced production of TNF-alpha (p<0.05), PCNA (p<0.05), and epithelial growth factor mRNA and enhanced production of Fas mRNA (p<0.01). The expression of TNF-R1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
1
2
1
3
Order By: Relevance
“…Several authors have described the presence of TNF-α in different benign hyperplasias [18][19][20]. In the present study, we detected TNF-α and TNF-R1 in more than 84% of cases with benign ovarian lesions, whereas TNF-R2 was detected in a low number of cases (24%).…”
Section: Discussionsupporting
confidence: 59%
“…Several authors have described the presence of TNF-α in different benign hyperplasias [18][19][20]. In the present study, we detected TNF-α and TNF-R1 in more than 84% of cases with benign ovarian lesions, whereas TNF-R2 was detected in a low number of cases (24%).…”
Section: Discussionsupporting
confidence: 59%
“…In the present study, the increase in uterine TNFα is in harmony with the results of Abdelzaher et al [38] who reported a significant increase in TNFα in estradiol valerate-induced EH in rats. In contrast, the expression of the IL10 gene did not change in patients with EH [39], although in the current study, EH was associated with decreased IL10 expression. The EH+IRB-treated rats showed lower uterine TNFα and enhanced IL10 compared to EH untreated rats.…”
Section: Discussioncontrasting
confidence: 95%
“…However, for both receptors, the immunostaining intensities were scant, and this suggests that TNF-α has little effect on benign breast pathologies. Several authors have described the presence of TNF-α in different benign hyperplasias, including prostatic, (23) gallbladder mucosa, (30) gastric (31) and endometrial (32) hyperplasias. However, the effects mediated by TNF-α in these hyperplasias would be slight, as expression of both receptor types was scant.…”
Section: Discussionmentioning
confidence: 99%